Fuzzy analytical hierarchy process (F-AHP) method in evaluating E-wallet payment system in Malaysia - Soo-Fen, Fam; Chuan, Zun Liang; Wahjono, Sentot-Iman; Zaini, Nur Dalila (Philstat.org.ph, 2022)
A digital wallet also known as "E-wallet" refers as financial transaction that proceeding payment through an electronically system and device. The digital revolution continues to transform most of our everyday lives especially in this challenging world of pandemic Covid-19. In the new norms, government encouraged to utilize e-wallet as a way to prevent contagious by incentive of eBelia also ePenjana. As e-wallet actively used, this has increased the mass growth of E-wallet providers. Due to accumulation of e-wallet, the aim is to provide overall ranking towards e-wallet payment system for consumers in selecting efficient payment system for transaction. For the solution, this research has utilized the Multi-Criteria Decision Making (MCDM) method of Fuzzy Analytical Hierarchy Process (FAHP). In order to assist consumers in selecting a higher-quality digital wallet payment system, this study assess 4 criteria of E-wallet Payment System quality, with the top 3 alternative of e-wallet providers. Based on the highest weightage value, the most preferable criteria and alternatives for e-wallet will established. Touch 'n Go had become the preferable e-wallet with weightage of 0.419. Among all criteria, security became the most essential factor in selecting e-wallet. In the future, researchers are encouraged to use another approach in MCDM.